3D graphene decorated Na4Fe3(PO4)2(P2O7) microspheres as low-cost and high-performance cathode materials for sodium-ion batteries. (February 2019) - Yuan, Tianci; Wang, Yanxia; Zhang, Jiexin; Pu, Xiangjun; Ai, Xinping; Chen, Zhongxue; Yang, Hanxi; Cao, Yuliang
Abstract: Sodium-ion battery has emerged as one of most promising technologies for large-scale energy storage system, and hence has stimulated extensive exploration of applicable electrode materials with low cost and superb electrochemical properties. Herein, 3D graphene decorated Na4 Fe3 (PO4 )2 (P2 O7 ) microspheres as a low-cost and environmentally friendly cathode material are synthesized by using a facile spray-drying method. The as-prepared NFPP@rGO composite exhibits a high reversible capacity of 128 mAh g −1 at 0.1 C, a superior rate capability (35 mAh g −1 at 200 C), and a long cycling life (62.3% capacity retention over 6000 cycles at 10 C). The excellent electrochemical performance is attributed to combined advantages of graphene coating on the surface of nanoparticles and the flexible 3D graphene network, which not only improve the electronic conductivity, but also accommodate the structural stress of the material during charging and discharging. Therefore, the NFPP@rGO microsphere with superior electrochemical performances, low-cost raw materials, simple synthetic route and high thermal stability is considered as a very attractive cathode electrode for sodium ion battery. Graphical abstract: Highlights: NFPP@rGO microsphere is synthesized by using a facile spray-drying method. The NFPP@rGO composite exhibits high electrochemical performance for Na ion storage. The excellent performance is attributed to combined advantages of graphene coating and 3D network.